Strain, Coping, and Socioeconomic Status: Coping Histories and Present Choices - Botchkovar, Ekaterina (Journal of quantitative criminology, 2013)
Objectives Using household survey data from three major cities in foreign countries, we add to research concerning General Strain Theory (GST) by focusing on aspects that have been ignored or under-researched. First, we address questions concerning SES variations in the operation of the processes of GST, with particular focus on whether various relationships specified by the theory are more likely in the lower SES group. Second, we explore the extent to which prior coping strategies influence subsequent coping choices. Finally, we seek to determine the links between SES, coping histories, and subsequent coping choices. Methods The study analyzes the effects of past and contemporaneous strain/negative emotions and prior coping efforts on various coping strategies across three SES groupings using negative binomial, ordered logit, and OLS regression. Results We find that, with some variations, the basic processes of GST are operative across all SES categories. However, whereas strain appears to have a moderate association with alcohol-related and criminal coping strategies, avoidant coping appears to be largely irrelevant for anybody who faces strain. Our data also demonstrate that specific forms of prior coping partially influence the types of coping employed later. But, with few exceptions, these effects are not more pronounced among those of lower SES. Conclusion In sum, our findings suggest that individuals in various SES groupings may prefer certain types of coping, whereas different types of attempted coping may predispose individuals to specific forms of subsequent adaptation.